Odškodninska odgovornost novinarjev in urednikov po 147. členu OZ - Mežnar, Špela (Delavci in delodajalci, 2014)
This article focuses on the situation of the direct liability of the employers for damages caused by the staff journalists and editors (employees) for third parties in the course of their work. The position of the Slovenian Supreme Court, according to which staff journalists and editors (employees) are not subject to the privilege of exclusive liability of their employer (media company) for damage caused by ordinary negligence, is neither justified nor theoretically correct. This applies to both arguments, applied by the highest court: first, it is not true that the intent to write an article per se contains the intent to cause damage. Second, Article 6 (and Article 18) of the Media Act do not constitute a lex specialis (as an exception) in relation to 147 Code of Obligation. The author exposes the controversy of the case law according to which such strict rules of direct personal responsibility are being applied for the journalists and editors that exculpation on the grounds of Article 147 of the Code of Obligations is virtually impossible. The article analyses the case law and comments on controversial issues.
Keywords: časnikarstvo; delodajalci; novinarji; novinarstvo; odškodninska odgovornost; osebna odgovornost; uredniki